2011
DOI: 10.2169/internalmedicine.50.4395
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Response of Dropped Head Sign to Treatment with Steroid in Parkinson's Disease: Report of Three Cases

Abstract: Neck dystonia is the most common cause of dropped head sign in parkinsonism. Isolated neck extensor myopathy, which is a rare condition, can also cause dropped head sign in parkinsonism, but no improvement has been achieved with immunosuppressive therapy. We report three cases of treatable neck extensor myopathy causing dropped head sign in patients with Parkinson's disease. Needle electromyography and magnetic resonance imaging suggested a restrictive active myopathy affecting neck extensor muscles. All cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Electromyography (EMG) showed short-duration, low-amplitude motor unit potentials with reduced recruitment patterns in the paraspinal muscles at the C5 spinal Because the STIR high signal intensity was limited to the posterior neck muscles, we considered isolated neck extensor myopathy (INEM). [1][2][3] However, based on extensive muscle atrophy and radiation-associated findings, the patient was diagnosed with DHS due to chemoradiotherapy. Unfortunately, he died from aspiration pneumonia a year later.…”
Section: Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electromyography (EMG) showed short-duration, low-amplitude motor unit potentials with reduced recruitment patterns in the paraspinal muscles at the C5 spinal Because the STIR high signal intensity was limited to the posterior neck muscles, we considered isolated neck extensor myopathy (INEM). [1][2][3] However, based on extensive muscle atrophy and radiation-associated findings, the patient was diagnosed with DHS due to chemoradiotherapy. Unfortunately, he died from aspiration pneumonia a year later.…”
Section: Descriptionmentioning
confidence: 99%
“…Because the STIR high signal intensity was limited to the posterior neck muscles, we considered isolated neck extensor myopathy (INEM) 1–3. However, based on extensive muscle atrophy and radiation-associated findings, the patient was diagnosed with DHS due to chemoradiotherapy.…”
Section: Descriptionmentioning
confidence: 99%
“…Patients with severe pain in the extensor muscles may present with acute inflammation. Hemmi et al reported that steroid pulse therapy had significant effects on DHS caused by myopathy [ 4 ]; however, it did not have an effect on DHS caused by other conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For those patients who showed any evidence of focal myopathy, we attempted steroid treatment, and evaluated their effects against DHS. A preliminary report regarding three cases of the present series has been published elsewhere …”
Section: Introductionmentioning
confidence: 99%